"Detrimental to the Team Dynamic": Exploring College Student-Athlete Dissent. (February 2023) - Rey, Rikishi T.; Johnson, Zac D.
To properly manage college student-athlete dissent, stakeholders (e.g., coaches, teammates, administration, athletic trainers, etc.) must first recognize the situations that cause athletes to dissent. Although athletic dissent is not a new concept, to date, it has only been examined at the high school level. To fill this gap, this study begins to explore this issue at the college level by examining the triggering agents that cause college student-athletes to communicate dissent. Participants ( N = 72) from 11 different sports were asked to complete multiple narratives in response to open ended questions after reflecting on a time where they communicated dissent. Results of a thematic analysis indicate that there are eight triggering agents of dissent, demonstrating distinct differences between high school and college student-athlete dissent due to various contextual factors. These findings highlight the needs and desires of college student-athletes which can help coaches, administration, and other stakeholders to promote positive college student-athlete experiences.